Principles and practice of anesthesia for thoracic surgery - Slinger, Peter (Springer, 2011)
Principles and Practice of Anesthesia for Thoracic Surgery will serve as an updated comprehensive review covering not only the recent advances, but also topics that haven't been covered in previously published texts: extracorporeal ventilatory support, new advances in chest imaging modalities, lung isolation with a difficult airway, pulmonary thrombo-endarterectomy, and chronic post-thoracotomy pain. Additionally, the book features clinical case discussions at the end of each clinical chapter as well as tables comprising detailed anesthetic management.